Anna Austin Ingleman, A Convergence of Passion and Career: Dramatics in Independence, Kansas (1900s-1930s) - Black, Molly (Kansas State University, The Chapman Center for Rural Studies, 2017)
This study involves the impact by teacher Anna Ingleman in Independence, Kansas during the early 20th century on the dramatics and theatre of the school, town, and the legacy they inspired. This study includes yearbook photographs and articles, dissertations, and newspaper articles from various Kansas papers.
Molly Black, “Anna Austin Ingleman, A Convergence of Passion and Career: Dramatics in Independence, Kansas (1900s-1930s),” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/247.
Keywords: Anna Ingleman; Dee-Dee Club; Montogomery County; Independence High School; I Love Lucy; Kansas